2020
DOI: 10.1177/1043454220917686
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Symptom Assessment in Children and Adolescents With Advanced Cancer Undergoing Hematopoietic Stem Cell Transplantation

Abstract: Background/Purpose: Effective symptom assessment and management for children with advanced cancer undergoing hematopoietic stem cell transplantation (HSCT) is critical to minimize suffering. The purpose of this subanalysis was to compare feasibility of electronic data collection data and symptom prevalence, frequency, severity, and distress from children with advanced cancer undergoing HSCT with a non-HSCT cohort. Method: An abbreviated Pediatric Quality of Life and Evaluation of Symptoms Technology Memorial S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…These assessment findings include: fatigue, hair loss, depression, nausea, confusion, pain, anger, bleeding, diarrhoea and mouth sores/mucositis. Other findings were insomnia, neuropathy, neutropenia night sweats, weight loss and sensory changes that are found in patients who are on chemotherapy treatment (Linder & Wawrzynski, 2018; Silva et al., 2016; Ward et al., 2020). These participants' stories revealed that they played with the children and regularly watched the children to monitor their progress.…”
Section: Discussionmentioning
confidence: 99%
“…These assessment findings include: fatigue, hair loss, depression, nausea, confusion, pain, anger, bleeding, diarrhoea and mouth sores/mucositis. Other findings were insomnia, neuropathy, neutropenia night sweats, weight loss and sensory changes that are found in patients who are on chemotherapy treatment (Linder & Wawrzynski, 2018; Silva et al., 2016; Ward et al., 2020). These participants' stories revealed that they played with the children and regularly watched the children to monitor their progress.…”
Section: Discussionmentioning
confidence: 99%
“…Here, five potential topics are generated by topic analysis. Topic 1 (3170 studies) consists of subjectrelated studies, and various researches 39,40 presented lots of…”
Section: Discussionmentioning
confidence: 99%
“…Here, five potential topics are generated by topic analysis. Topic 1 (3170 studies) consists of subject-related studies, and various researches 39,40 presented lots of subjects such as patient, child, and family in nursing informatics. For the hospital-based research group (topic 2, 2555 studies), many studies focused on medical costs or medication errors 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Janicsâk et al (2013) have reported that patients' physical, social, emotional, and functional well-being decreased after HSCT [39]. In a study comparing the symptoms of cancer patients who underwent HSCT and those who did not undergo HSCT, Ward et al (2020) have reported that the "lack of appetite" score in patients who underwent HSCT was 10.66 ± 23.2, while other cancer patients' score was 6.07 ± 15.6 [40]. After HSCT, protective isolation was needed and this contributed to the physiological problems among patients [41].…”
Section: Discussionmentioning
confidence: 99%